Mathematical modelling of thin layer drying process of long green pepper in solar dryer and tinder open sun - Akpinar, E. Kavak; Bicer, Y. (Pergamon-Elsevier Science Ltd, 2008)
An experimental study was performed to determine the thin layer drying characteristics in a solar dryer with forced convection and tinder open sun with natural convection of long green pepper. An indirect forced convection solar dryer consisting of a solar air collector and drying cabinet was used in the experiments. Natural sun drying experiments were conducted for comparison at the same time. The constant rate period is absent from the drying curves. The drying process took place in the falling rate period. The drying data were fitted to 13 different mathematical models. Among the models, the logarithmic model for forced solar drying and the Midilli and Kucuk model for natural sun drying were found best to explain the thin layer drying behaviour of long green peppers. The performance of these models was investigated by comparing the coefficient of determination (R), reduced chi-square (chi(2)) and root mean square error (RMSE) between the observed and predicted moisture ratios. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: solar drying; natural sun drying; forced drying; thin layer drying models; long green pepper